2022
DOI: 10.1021/acsfoodscitech.2c00133
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Polyphenol and Reductone Antioxidants in the Caramelization Product of N-Acetylglucosamine

Abstract: Caramelization is a nonenzymatic browning reaction of saccharides that occurs under thermal treatment. In this study, the radical scavenging activity of the thermal reaction products (caramels) from three modified hexoses [fucose, galacturonic acid, and N-acetylglucosamine (NAG)] was evaluated. These three caramelization products showed more potent activity than that of the thermal reaction product from glucose, with the most significant activity observed in the product of NAG. A polyphenol and a reductone wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…As far as we can tell, our study is the first to identify derivatives of isorhamnetin in the leaves of wild strawberry. Compounds 19,23,29,31,32,41,42,and 51 were identified according to recent findings [36] as quercetin-3-rhamnoside, quercetin-3-pentoside, kaempferolpentosyl-hexoside, quercetin-acetyl-hexoside, kaempferol-acetyl-hexoside, quercetin-acetylrutinoside, kaempferol-acetyl-rutinoside, and quercetin-pentosylhexoside, respectively. Compounds 33, 43, 45, 49, and 50 were identified according to the published data [17] as isorhamnetin-3-O-glucoside, quercetin-3-O-dihexoside, isorhamnetin-pentosylhexoside, quercetin, and kaempferol, respectively.…”
Section: Effects Of Extraction Methods On Phenolic Profilementioning
confidence: 99%
See 1 more Smart Citation
“…As far as we can tell, our study is the first to identify derivatives of isorhamnetin in the leaves of wild strawberry. Compounds 19,23,29,31,32,41,42,and 51 were identified according to recent findings [36] as quercetin-3-rhamnoside, quercetin-3-pentoside, kaempferolpentosyl-hexoside, quercetin-acetyl-hexoside, kaempferol-acetyl-hexoside, quercetin-acetylrutinoside, kaempferol-acetyl-rutinoside, and quercetin-pentosylhexoside, respectively. Compounds 33, 43, 45, 49, and 50 were identified according to the published data [17] as isorhamnetin-3-O-glucoside, quercetin-3-O-dihexoside, isorhamnetin-pentosylhexoside, quercetin, and kaempferol, respectively.…”
Section: Effects Of Extraction Methods On Phenolic Profilementioning
confidence: 99%
“…However, our study was performed on leaves, not fruit. On the other hand, compounds formed by caramelization [29] and the Maillard reaction [26] may not have a phenolic structure but may have antioxidant properties. In addition, thermal decarboxylation of hydroxycinnamic acids to the corresponding 4-vinyl derivatives should also be considered, since decarboxylation reduces the reduction and antiradical activity of the corresponding phenolic acids in a homogeneous polar medium [30].…”
Section: Effects Of Extraction Parameters On Yield Of Phenolicsmentioning
confidence: 99%
“…In food processing, the application of GlcNAc is still limited, although several applications have been reported, including supplementation of GlcNAc in food products, as a growth promotor for probiotics in fermented milk (Chen et al 2004) and as a sweetener in food and beverages (Wassenaar, 2004). Recently, Doi et al (2022) reported that caramelized GlcNAc has a great potential to be an antioxidant agent to prevent oxidative deterioration in food.…”
Section: N-acetylglucosaminementioning
confidence: 99%